Influences of fatigue and anticipation on female soccer players’ biomechanical characteristics during 180° pivot turn: implication for risk and prevention of anterior cruciate ligament injury - Zou, Limin; Zhang, Xiaochun; Jiang, Ziang; Wu, Xie; Zhang, Qiang (Frontiers in Physiology, 2024)
Introduction: Athletes’ capability to perform activities with body rotation could be weakened by fatigue accumulation. Making pivot turning in unanticipated scenarios after fatigue may greatly challenge athletes’ ability to adapt rational motion strategies, elevating the risk of anterior cruciate ligament (ACL) injury. This study aimed to investigate the effects of fatigue and anticipation on biomechanical risk factors of ACL injury during 180° pivot turns in female soccer players. Results: Compared to the anticipated conditions, the approach speed was significantly lower in the unanticipated tests (P < 0.0001). Lower-limb kinematics showed varied angular patterns across conditions: greater hip joint variations in flexion, abduction, and internal rotation during unanticipated turns; consistent knee joint flexion and ankle plantarflexion with dorsiflexion observed mid-turn. Significant interactions (P = 0.023 to P = 0.035) between fatigue and anticipation influenced hip joint angles. Anticipation effects were notable at initial contact and peak ground reaction force, increasing hip, knee, and ankle joint angles (P < 0.0001 to P = 0.012). Participants showed consistent ground reaction force (GRF) patterns during pivot turns across fatigue and anticipation conditions, with the 1st peak occurring approximately 10% into the turn period. Significant interaction effects (P = 0.016) between fatigue and anticipation were observed for knee flex/extension moments at the 1st peak vertical GRF. Anticipation significantly increased 1st peak vertical (P < 0.0001), anteroposterior (P < 0.0001), and mediolateral (P < 0.0001) GRFs. Fatigue increased 1st peak vertical (P = 0.022), anteroposterior (P = 0.018), and mediolateral (P = 0.019) GRFs. Post-fatigue, participants exhibited reduced 1st peak GRFs and loading rates compared to pre-fatigue conditions, with higher rates observed in unanticipated turns (vertical GRF: P = 0.030; anteroposterior GRF: P < 0.0001). Conclusion: Female soccer players’ lower-limb Biomechanical characterization could be greatly affected by the change of anticipatory scenarios. With the associated increase of GRF, the risk of their ACL injury might be elevated. Fatigue affected female soccer players’ abilities on movement performances, but the interaction of these two factors could potentially weaken their knee’s functions during pivot turns. Cognitive training on unanticipated tasks may be important for rehabilitation training after ACL injury.